Epidermotropic B-Cell Lymphoma: A Unique Subset of CXCR3-Positive Marginal Zone Lymphoma. (February 2016) - Magro, Cynthia M.; Momtahen, Shabnam; Lee, Bonnie A.; Swanson, David L.; Pavlovic, Milos D.
Abstract : Background: Epidermotropic B-cell lymphoma is a very rare entity that has primarily been reported in the literature as anecdotal case reports. The majority of the reported cases exhibit a diffuse skin rash affecting middle-aged to older adults with a male predominance. The exact mechanism of marginal zone B-cell localization to the epidermis is unclear. Material and Methods: To describe a very rare subset of cutaneous B-cell lymphoma and explore potential pathogenetic mechanisms for the epidermotropic tendency, the hospital database and literature review was conducted to isolate cases of epidermotropic B-cell lymphoma. Routine hematoxylin and eosin stain followed by selective phenotypic studies. Results: Two of the cases were encountered in the hospital database, whereas 5 cases have been previously reported; material was requested on previously reported cases and was received on 3 of them. In one of the 2 cases encountered in our database, the patient presented with a progressive skin rash over 7 months resembling pityriasis rosea. Subsequent to a diagnosis of B-cell lymphoma, further staging revealed bone marrow involvement. The other patient, an elderly female, presented with isolated nodules. The biopsies of both cases showed areas of superficial band-like lymphocytic infiltration with large monocytoid appearance and an epidermotropic pattern of lymphocyte migration into the epidermis. Neoplastic cells were extensively positive for CD20, CD79a, and BCL-2 and negative for CD10 and BCL-6. Of interest, a similar pityriasis rosea–like presentation was encountered in the cases reported in the literature. All patients were elderly males with established bone marrow, peripheral blood, and spleen involvement several months to years after the initial cutaneous presentation in 3 of them. None of the patients to date have died of lymphoma. CXCR3 epidermotropic B cells were detected in both our cases and in 3 of the 3 previously published cases. Conclusions: Epidermotropic B-cell lymphoma represents a subset of marginal zone lymphoma characterized by a papulosquamous rash most frequently resembling pityriasis rosea, occurring almost exclusively in older males. We speculate that aberrant expression of CXCR3 in marginal zone lymphoma of the skin is associated with migration of lymphoma cells to the epidermis and could lead to an epidermotropic pattern given the known role of CXCR3 expression in neoplastic T cells in the localization of mycosis fungoides to the epidermis. There is a tendency toward bone marrow, spleen, and peripheral blood involvement.